A Comprehensive Bibliographic Review Concerning the Efficacy of Organic Acids for Chemical Peels Treating Acne Vulgaris - Șoimița Emiliana Măgerușan; Gabriel Hancu; Aura Rusu (Molecules, 2023)
Acne vulgaris stands out as the most prevalent skin disorder among teenagers and young adults, causing physical discomfort and considerable economic and psychological burdens on individuals and society. A wide range of topical and systemic therapies are available in acne treatment. Chemical peeling is a skin resurfacing technique designed to rebuild healthy skin using exfoliating substances, a simple and affordable process with various dermatological uses. Chemical peels, classified as superficial, medium, and deep, have been utilized for acne vulgaris and multiple other skin issues. In these chemical peels, a diverse range of chemical substances is employed, each with its unique mode of action. Among these, α-hydroxy and β-hydroxy acids have gathered attention for their efficacy in reducing acne lesions and enhancing overall skin appearance. Acids, such as salicylic acid, glycolic acid, or lactic acid, are commonly used in chemical peels due to their exfoliating and sebum-regulating properties. Despite the widespread use of these acids, there exists a lack of consensus regarding the most effective acid type and concentration for treating acne-prone skin. This review aims to bridge this knowledge gap by evaluating the effectiveness and safety of various organic acids used in chemical peels specifically for acne-prone skin. The findings of this comprehensive bibliographic review indicate that organic acid-based chemical peels represent effective and safe treatment options for individuals with acne-prone skin. Their adaptability sets these treatments apart; the choice of organic acid can be tailored to meet individual patient needs and tolerability levels. This personalized approach ensures that patients receive optimal care while minimizing the risks associated with the treatment. As research in this field progresses, it is anticipated that a more nuanced understanding of the ideal acid type and concentration will emerge, further enhancing the efficacy and safety of chemical peels for acne-prone skin.